Disease resistance traits of IPB-D2 chickens: Characterization of IgY concentrations, Newcastle disease antibody titers, and leukocyte profiles - Dwi Lestari; Sri Murtini; Niken Ulupi; Asep Gunawan; Isyana Khaerunnisa; Anneke Anggraeni; Cece Sumantri (Veterinary World)
Background and Aim: The IPB-D2 chicken, a potential disease-resistant local Indonesian line, has been developed to improve poultry health and productivity for small-scale farmers. This study aimed to characterize the disease resistance traits of IPB-D2 chickens by analyzing key immunological parameters, including immunoglobulin Y (IgY) concentration, Newcastle disease (ND) antibody titers, and leukocyte profiles.